Pertunjukan Wayang Babad Nusantara: Wahana Pengajaran Nilai Kebangsaan bagi Generasi Muda - Sunardi -; Sugeng Nugroho; Kuwato - (PANGGUNG, 2016)
ABSTRACT Wayang Babad Nusantara  represents a creation  of a shadow puppet show which  used as a means of transmission  of nationalism  values  towards younger  generations.  This type  of show has the aspect  of innovations  in several  elements  of pakeliran,  which are: the heroic story  of National  heroes’ struggle, the authentic  puppets bas on the reinterpretation  of the figure in the history, a new musical score, and the scene-system with the shadow puppet show structure.  This show is interestingly  wrapped with the story of Gajah Mada. The spirit of these figure  serves as the good example for young  generations  to love their  country.  The  nationalism  value,  which contain  the teaching  of patriotism  and allegiance can build the awareness  of the children  of the nation  so that they will always  love the land  of Indonesia. Keywords: Babad shadow puppet, nationalism  values,  young  generations     ABSTRAK Wayang Babad Nusantara merupakan rekayasa model pertunjukan wayang yang dipergunakan sebagai wahana transmisi nilai-nilai kebangsaan bagi generasi muda. Pertunjukan wayang ini memiliki kebaruan dalam berbagai unsur pakeliran, yaitu: cerita sejarah perjuangan pahlawan bangsa, boneka wayang hasil reinterpretasi dari figur tokoh, musik komposisi baru, dan sistem pengadegan dengan struktur pertunjukan wayang. Pertunjukan wayang ini dikemas secara menarik dengan menyajikan cerita Gajah Mada. Spirit perjuangan tokoh Gajah Mada ini memberikan suri teladan bagi generasi muda untuk selalu cinta tanah air. Nilai kebangsaan yang memuat ajaran mengenai patriotisme dan nasionalisme memberikan kesadaran dan menggugah kesadaran anak bangsa untuk selalu mencintai Tanah Air Indonesia. Kata kunci: wayang babad, nilai kebangsaan, generasi muda